2009
DOI: 10.1007/s10689-009-9302-4
|View full text |Cite
|
Sign up to set email alerts
|

Selection of patients with germline MLH1 mutated Lynch syndrome by determination of MLH1 methylation and BRAF mutation

Abstract: Lynch syndrome is one of the most common hereditary colorectal cancer (CRC) syndrome and is caused by germline mutations of MLH1, MSH2 and more rarely MSH6, PMS2, MLH3 genes. Whereas the absence of MSH2 protein is predictive of Lynch syndrome, it is not the case for the absence of MLH1 protein. The purpose of this study was to develop a sensitive and cost effective algorithm to select Lynch syndrome cases among patients with MLH1 immunohistochemical silencing. Eleven sporadic CRC and 16 Lynch syndrome cases wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…In agreement with previous reports, the sensitivity of the absence of BRAF mutation is very high in identifying MLH1 mutation carriers 16,18,21,39 (Table 3 and Supplementary Data Table 5). A single false-negative was identified adding to the increasing number of LS tumors harboring a BRAF mutation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with previous reports, the sensitivity of the absence of BRAF mutation is very high in identifying MLH1 mutation carriers 16,18,21,39 (Table 3 and Supplementary Data Table 5). A single false-negative was identified adding to the increasing number of LS tumors harboring a BRAF mutation.…”
Section: Discussionsupporting
confidence: 92%
“…First, the low prevalence of BRAF mutations observed in our selected population (11% of MSI tumors and 20% of those lacking MLH1 protein expression). This is in the lower range of reported series 16,18,21,39 but likely to reflect the experience of referral centers. 21 Second, the significant number of LS cases and MLH1 germline carriers analyzed allows more accurate estimates.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The somatic BRAF V600E (c.1799T>A mutation hotspot) mutation is highly associated with MLH1 promoter methylation in colorectal tumours (not endometrial), but not all methylated tumours have the BRAF mutation 71,78,255,256 . It has been suggested that colorectal tumours with MLH1 promoter methylation and/or the BRAF V600E mutation should not be screened for MMR mutations [256][257][258] . Furthermore, testing for MLH1 methylation and the BRAF V600E mutation appears to have become increasingly utilised in molecular and genetic testing algorithms in clinical practice to discriminate sporadic MSI-H CRC from MSI-H CRC in LS.…”
Section: Mlh1 Promoter Methylation and Braf V600ementioning
confidence: 99%